Structure and chemical bond of carbodiylide complexes [W(CO)5{C(ECp*)2}] (E = B to Tl): DFT calculations - Ai Nhung, Nguyen Thi (Vietnam Journal of Chemistry, 2017)
The bonding of the carbodiylide complexes [(CO)5W-{C(ECp*)2}] (W5-C1E) was calculated at the BP86 level with the basis sets def2-SVP, def2-TZVPP, and TZ2P+. The nature of the (CO)5W-{C(ECp*)2} bonds was analyzed by energy decomposition method. The calculated structures of complexes show that all ligands C(ECp*)2 (C1E) are bonded in a tilted orientation relative to the fragment W(CO)5 in W5-C1E and the tilting angle become much more acute when E becomes heavier. Analysis of the bonding reveals that [(CO)5W–{C(E’Cp*)2}]  donation in W5-C1B come from the s-lone-pair orbital of C(BCp*)2, while [(CO)5W–{C(E’Cp*)2}]  donation in the strongly tilted bonded complexes when E’ = Al to Tl comes from the p-lone-pair orbital of the carbodiylides C(E’Cp*)2. The W-C bonds have not only (CO)5W¬C(ECp*)2 strong s-donation but also a significant contribution π-donation and the trend of the W-C bond strength in W5-C1E complexes. EDA-NOCV calculations reveal that C(ECp*)2 ligands in W5-C1E complexes  are strong s-donors and weak p-donors which make them good spectator ligands that are well-suited for synthesizing robust catalysts for a variety of applications. Keywords. Carbodiylides, energy decomposition analysis, bond dissociations energy, bonding analysis.